ANALISIS PENYAJIAN LAPORAN KEUANGAN BERDASARKAN PENERAPAN STANDAR AKUNTANSI PEMERINTAH (PSAP) NO.01 PADA KANTOR CAMAT TANGGETADA - Risal, Muh Afdal; Sabarudin, Sabarudin; Ilham, Surianto (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study is to determine the implementation of PSAP 01 concerning the Presentation of Government Financial Statements in the Tanggetada Sub-district Government. This study examines the problem using a qualitative method. Sugiyono, (2013) stated that this study has a post-optimism basis which means that the key instrument in the study is the researcher himself with data collection techniques using triangulation techniques and has results that emphasize more on meaning. This study focuses on the balance of elements presented in the financial statements of the Tanggetada Sub-district Government with PSAP No. 01. The Tanggetada District Government has prepared a financial report as a form of accountability for regional financial management, in this case the Regional Revenue and Expenditure Budget (APBD) of Kolaka Regency which includes the Tanggetada District Government in a timely manner. This Financial Report provides relevant information regarding the financial position and performance achievements of the Tanggetada District Government. Keywords: Presentation Analysis, Financial Reports, PSAP 01